Relationship of milk production in Angus and Simmental cows with milk expected progeny differences (EPDs) and calf weaning weight - Marston, T.T.; Simms, D.D.; Schalles, R.R.; Zoellner, K.O.; Martin, L.C.; Fink, G.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Spring and fall calving Angus (n==86) and Simmental (n==96) cows at three different locations in Kansas were used to evaluate the relationships between milk production, Milk Expected Progeny Difference (Milk EPD), and calf weaning weight. A change of 1 lb in Milk EPD resulted in 4.95 lb change in calf weaning weight in Angus and 4.60 lb in Simmental. Each lb increase in Milk EPD predicted a 69.87 lb increase in total lactation milk production in Angus and 70.741b in Simmentals. Positive correlations were .40 and .64 between Milk EPD and total milk produced per lactation and .24 and .49 between Milk EPD and calf weaning weight for Angus and Simmental, respectively. Milk EPDs can be used as genetic selection tools to influence milk production levels and make corresponding changes in calf weaning weights.
Keywords: Beef; Angus; Simmental; Milk; Lactation; Calf weaning weight; Milk expected progeny differences